Rheology, In Vitro Digestion and Functional Properties of Sagittaria sagittifolia L. Resistant Starch as Affected by Different Preparation Methods. (31st March 2022) - Feng, Yuqin; Juliet, Igbokwe Chidimma; Qin, Wei; Duan, Yuqing; Gao, Xingxing; Liu, Qiaoling; Zhang, Haihui; Ma, Haile
Abstract: In this study, the effects of different preparation methods on the rheology, in vitro digestion, and functional properties of Sagittaria sagittifolia L. resistant starch (ARS) are investigated. Compared with S. sagittifolia L. native starch (ANS), the ARS that is prepared by subcritical water (SW‐ARS), ultrasonic‐assisted subcritical water (USW‐ARS), autoclaving (AM‐ARS), and ultrasonic‐assisted autoclaving (UAM‐ARS) show higher dilatancy, light transmittance, water and oil retention, but lower solubility and in vitro digestibility. In addition, the differences between the storage modulus ( G ′) and loss modulus ( G ″) of ARS are significantly lower than that of ANS. Moreover, there is a cross phenomenon between G ′ and G ″ of ARS after ultrasonic pretreatment. Besides, the ability of ARS to reduce the pH value of fermentation broth is much lower than that of ANS, among which SW‐ARS is the weakest, USW‐ARS has the highest acetic acid and formic acid production during in vitro digestion fermentation. These results suggest that the ARS prepared by different methods is suitable for the developing of starch‐based material with excellent properties. Abstract : The resistant starch (RS) prepared by different methods exhibit different structural and physicochemical properties, which further affect its rheology, in vitro digestion, and functional properties. The ARS prepared by different methods is suitable for the developing of starch‐based material with excellent properties. In actual production and processing, an appropriate preparation method can be selected according to the processing requirements.